2010
DOI: 10.3109/00048674.2010.490520
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prevalence of Major Depression in an Australian Community Sample Between 1998 and 2008

Abstract: The prevalence of major depression increased significantly in South Australia over the last decade and there was a reduction in mental health status and an increase in persons reporting poor health. Unexpectedly, having poor or fair mental health literacy was significantly protective for major depression. Ideally, public health initiatives should result in an improvement in health, but this did not appear to have occurred here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 44 publications
4
63
1
1
Order By: Relevance
“…Between 1991-92 to 2001-2, one-year prevalence rates of major depression increased from 3.33% to 7.06% in a community population of American adults (Compton et al, 2006). Increases have also been observed in Australian communities with prevalence rates rising from 6.8% to 10.3% between 1998 and 2008 (Goldney et al, 2010). While these increased rates of depression may be due, in part, to improvements in diagnostic recognition, changes in diagnostic criteria and increased community acceptance of this condition, contemporary lifestyles might also explain why depression is on the rise.…”
Section: Introductionmentioning
confidence: 70%
“…Between 1991-92 to 2001-2, one-year prevalence rates of major depression increased from 3.33% to 7.06% in a community population of American adults (Compton et al, 2006). Increases have also been observed in Australian communities with prevalence rates rising from 6.8% to 10.3% between 1998 and 2008 (Goldney et al, 2010). While these increased rates of depression may be due, in part, to improvements in diagnostic recognition, changes in diagnostic criteria and increased community acceptance of this condition, contemporary lifestyles might also explain why depression is on the rise.…”
Section: Introductionmentioning
confidence: 70%
“…However, research supporting this position has been inconsistent. Several studies have shown increases in recent years, 1,2 including among adolescents. [3][4][5][6][7] These studies have included parent reports from population samples 3,4 and physician diagnoses from electronic medical records.…”
mentioning
confidence: 99%
“…[27][28][29] Two large population studies and one large international multisite study in primary care found that self-rated health is associated with depression. 4,30,31 Although there is sound literature on the association between depression and self-rated health, we lack prognostic studies investigating the link between it and depression outcomes over time. Two studies suggest that self-rated health may be an important predictor of poor depression outcome.…”
mentioning
confidence: 99%